Diários de classe : sua história e contribuição aos estudos da alfabetização em Mato Grosso (1930-1970) - Fagundes, Luiza Gonçalves (2013)
The main objective of the research presented here was to analyze historical aspects of the “General Registers of the Educational Institution”, which in Mato Grosso were known as “Class Diaries” (grade books), with the belief that such documents serve as a source which contributes to studies related to the history of literacy. Due to the complexity of the subject, the research was organized chronologically to avoid dispersion. This approach facilitates the localization, recuperation, organization, selection and analysis of the sources. The methodological strategy chosen was the selection of the period from 1930 to 1970, which, respectively, represent the beginning and ending periods of the investigation. This time period was selected due to the fact that 1930 was the moment of consolidation, within the country as a whole, through single tabulation, of the National Educational Statistics, whose objective was to standardize the means of collecting such registers; and 1970, due to the fact that it was the last year in which school groups which were extinct by the law LDB 5.692/71 were registered. The choice of investigating Class Diaries pertaining to the elementary level was made based on the fact that literacy at the elementary level is of interest to both me, as a researcher, and to the research group ALFALE, which focuses directly on the development of literacy within the school setting and is also a group of which I am a member. This investigation is based on data collected by the research group ALFALE/CNPq/UFMT, of which the oldest examples date from 1930. Many research projects related to the History of Education are today interested in organizing and preserving the documents which are stored in administrative areas of schools. This renewed interest in such documents has taken place due to the restructuring of the researcher’s viewpoint, which observes that these materials (school documents) serve as a source of investigation which can be revisited, discovered and verified; or rather, this instrument of documentation represents established school cultures, and therefore responds to the forms of content, frequency and organization in educational institutions. The present research intends to contribute to reflection regarding certain aspects of the history of Class Diaries, through a reading and the construction of narratives of school cultures interlaced with contributions from studies based on the history of literacy practices in Mato Grosso. As a result, it is possible to affirm that Class Diaries are considered formal documents which present refined speech due to their comprobatory bias that expounds fixed data (student names, dates, content and grades) and variable data (the insertion of content related to the classroom context). Furthermore, such bookkeeping practices were created to evidence and serve as proof of teacher’s educational practices and student performance within the educational institution. This document was standardized and the teacher responsible for the class was obligated to fill in the required information. The teacher also was required to represent his/her practice in writing, clarifying through such register, in the complex spaces offered, the reality experienced within the school context. Thus, the Class Diaries have left clues about teaching practices and the evolution of the way in which this content is registered.